The water quality of swamp area in the Sawah Village, Kampar based on NSF-WQI - Hatmira Hatmira; Nur El Fajri; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract In the swamp area of the Sawah Village, the water quality is affected by pollutant originated from activities conducted around and in the swamp area. This research aims to determine the water quality of swamp in theSawahVillage based on NSF-WQI and conducted on March-April 2018. There were three stations with 3 sampling points/ station. Water samplingswere conducted 3 times, once/week.Water quality parameters measured were temperature,TSS,turbidity,pH, dissolved oxygen,BOD5, nitrate and phosphate. Datawere analyzed descriptively and pollution level was determined based on the formula of NSF-WQI. Resultsshown that the temperature was 28-30oC, TSS 3.0-1.0 mg/L, turbidity 1.8-18.5 mg/L, pH 5, dissolved oxygen 4.2-5.5 mg/L, BOD5 6.90- 17.6 mg/L, nitrate 0.146-0.210 mg/L, phosphate 0.178-0.279 mg/L. The value ofthe NSF-WQI was 45.10-51.82, indicates that waters of swamp area in the SawahVillagewas categorized as moderately to badly polluted. Keywords: water quality parameter, pollutant, quality standard